2016
DOI: 10.1002/tox.22289
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 2A inhibition and subsequent cytoskeleton reorganization contributes to cell migration caused by microcystin-LR in human laryngeal epithelial cells (Hep-2)

Abstract: The major toxic mechanism of Microcystin-LR is inhibition of the activity of protein phosphatase 2A (PP2A), resulting in a series of cytotoxic effects. Our previous studies have demonstrated that microcystin-LR (MCLR) induced very different molecular effects in normal cells and the tumor cell line SMMC7721. To further explore the MCLR toxicity mechanism in tumor cells, human laryngeal epithelial cells (Hep-2) was examined in this study. Western blot, immunofluorescence, immunoprecipitation, and transwell migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 55 publications
5
14
0
Order By: Relevance
“…It is well‐known that MC‐LR can seriously inhibit PP2A activity and cause cell toxicity in numerous cell lines . In our previous work, we observed similar results in different cell lines, and the response profile of PP2A to an MC‐LR insult in different cells presents its own distinguishing feature . In addition, we found that α4, a PP2A regulator, is closely related to the toxic effect of MC‐LR on HEK293 cells.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…It is well‐known that MC‐LR can seriously inhibit PP2A activity and cause cell toxicity in numerous cell lines . In our previous work, we observed similar results in different cell lines, and the response profile of PP2A to an MC‐LR insult in different cells presents its own distinguishing feature . In addition, we found that α4, a PP2A regulator, is closely related to the toxic effect of MC‐LR on HEK293 cells.…”
Section: Discussionsupporting
confidence: 75%
“…A variety of reports have shown that MC‐LR can disrupt the cytoskeletal architecture and lead to the reassembly or reorganization of cytosolic fibers, presumably due to inhibition of PP1 and PP2A, and the phosphorylation balance of the cytoskeleton‐related proteins plays a vital role in the regulation of cytoskeletal mobility and stability . A rearrangement of cell cytoskeleton induced by MC‐LR was observed in our previous study in different cell lines, including HL7702 . In addition, a protective role of α4 on cytoskeletal structure was observed when α4‐overexpressing HEK 293 cells were treated with MC‐LR.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…For example, Liu et al reported that MC-LR promoted proliferation and inhibited apoptosis in normal human liver cells (HL7702) (Liu et al, 2016). The study of Wang et al showed that MC-LR induced cytoskeleton reorganization, resulting in increased cell migration in human laryngeal epithelial cells (Hep-2) (Wang et al, 2017). However, the effect of MC-LR on prostate cancer (PCa) cells and normal prostate cells has yet been studied.…”
Section: Introductionmentioning
confidence: 99%